Directions to Ensure the Independence of Local Budgets - Uchqun Yunusovich, Uroqov; Obid Rakhmatullayevich, Meliyev; Akbar Akmirzayevich, Shernayev; Dildora Jamalovna, Jalolova; Khusnida Makhsud Kizi, Kulimova; Khabibullokh Ravshan Ugli, Razzokov (International Journal of Psychosocial Rehabilitation, 2020)
Creating an effective mechanism for the tax system and ensuring its effectiveness requires constant improvement of the tax mechanism, tax policy, and each type of tax. Today, there are still a number of problems with the implementation of local taxes and fees. In this article, we will focus on some of the problems associated with these local taxes and levies and how to solve them.